2000
DOI: 10.2466/pr0.2000.86.2.375
|View full text |Cite
|
Sign up to set email alerts
|

Cultural Similarities in Psychological Reactions to Infertility

Abstract: A 74-item especially developed and validated questionnaire for Iranian culture was administered three times to 37 Iranian infertile couples and 10 fertile couples acting as control group, namely, initial consultation, during treatment, and on completion of treatment. In view of parallel data also reported for Western patients interest centered on the results of two out of the five factors measured by the questionnaire, i.e., Psychological Stress and Social Behaviour. Analysis generally showed significantly hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
3

Year Published

2001
2001
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(11 citation statements)
references
References 11 publications
0
7
0
3
Order By: Relevance
“…Infertility is defined by the World Health Organization as a major medical and social problem and is considered to be a disease. Infertility can be stigmatizing and similar psychological reactions have been reported in different cultures (3, 4) . Different assisted reproductive technologies (ART) are established and available nowadays and the development of efficient infertility treatments has made biological parenthood possible for many couples who would otherwise have remained childless.…”
Section: Introductionmentioning
confidence: 68%
“…Infertility is defined by the World Health Organization as a major medical and social problem and is considered to be a disease. Infertility can be stigmatizing and similar psychological reactions have been reported in different cultures (3, 4) . Different assisted reproductive technologies (ART) are established and available nowadays and the development of efficient infertility treatments has made biological parenthood possible for many couples who would otherwise have remained childless.…”
Section: Introductionmentioning
confidence: 68%
“…Edelmann and Connolly (2000) found that distress did not increase after seven months of treatment, and Anderson et al (2003) found no differences for men or women on the Hospital Anxiety and Depression Scale or infertility-specific distress from just prior to initial visit to six months later. Nasseri (2000), however, found that psychological distress and social withdrawal are higher after treatment than during initial consultation. None of these studies was designed to allow for comparisons between those who received treatment and those who did not.…”
Section: Literature Reviewmentioning
confidence: 87%
“…Based on a national probability sample of women in the USA, King (2003) concludes that the effects of sub-fecundity on general anxiety disorder are not moderated by treatment. Some studies show that the length of treatment is not related to the level of stress (Anderson et al 2003), but several researchers have reported contradictory findings (Chiba et al 1997, Nasseri 2000). One unanswered question is whether changes in distress over time are a response to treatment or whether they are a result of the duration of infertility.…”
Section: Research On the Psychology Of Infertilitymentioning
confidence: 99%